Carbon flux in supraglacial debris over two ablation seasons at Miage Glacier, Mont Blanc massif, European Alps - Brown, Grace L.; Brock, Ben W. (Frontiers in Earth Science, 2023)
The cryosphere plays an important role in the global carbon cycle, but few studies have examined carbon fluxes specifically on debris-covered glaciers. To improve understanding of the magnitude and variability of the atmospheric carbon flux in supraglacial debris, and its environmental controls, nearsurface CO2 fluxes and meteorological variables were monitored over thick (0.23 m) and thin (0.04 m) debris at Miage Glacier, European Alps, over two ablation seasons, using an eddy covariance system. The CO2 flux alternates between downward and upward orientation in the day and night, respectively, and is dominated by uptake of CO2 in thick debris (mean flux = 1.58 g CO2 m -2 d -1 ), whereas flux magnitude is smaller and near parity net zero on thin debris (mean flux = -0.06 g CO2 m -2 d -1 ). These values infer a potential drawdown of >150 t CO2 km -2 over an ablation season, and >500 t CO2 (0.5 Gg CO2) for the whole debris-covered zone. The strong correlation of daytime CO2 flux magnitude with debris surface temperature suggests that atmospheric CO2 is consumed in coupled hydrolysis and carbonation-hydrolysis reactions at sediment-water interfaces in debris. Incoming shortwave radiation is key in heating debris, generating dilute meltwater, and providing energy for chemical reactions. CO2 drawdown on thin debris increases by an order of magnitude on days following rain-frost events, implying that frost shattering generates fresh reactive sediment, which is rapidly chemically weathered with the onset of ice melting. Net CO2 release in the night, and in the daytime when debris surface temperature is below 7 °C, is likely due to respiration by debris microorganisms. The combination of dilute meltwater, high temperature, and reactive mineral surfaces open to the atmosphere, makes supraglacial debris an ideal environment for rock chemical weathering. Debris-covered glaciers could be important to local and regional carbon cycling, and measurement of CO2 fluxes and controlling processes at other sites is warranted.